“Was de tael gansch het volk?” Comparatief onderzoek naar de Vlaamse en Slowaakse nationale beweging in de 19e eeuw: Een pleidooi om cultuurhistorisch te vergelijken in de neerlandistiek/ “Was the Language Representing the Whole Nation?” A Comparative Approach of the Flemish and Slovak National Movements in the 19th Century: A Plea for Comparative Research in Dutch Studies - Bossaert, Benjamin (Werkwinkel, 2015)
In this ongoing research we are going to have a look at the starting point for the burgeoning national feelings with two smaller nations: the Slovak and the Flemish national movement. Building on the methodological framework of nationalism researcher Miroslav Hroch, one can discern a threefold stage – model in the national movements of the smaller nations in Europe, which is a thesis still needing more empirical evidence. This article attempts to compare at least one aspect of early nineteenth-century nation – building: How were the literary societies functioning in both national movements? We are working in a time scope of the ﬁ rst half of the 19th century and ask ourselves the questions: until which extend reached literary societies? What was their impact? Which people were their readers, their public? Was their language, and their language-spreading aim representative for the whole nation? What similarities and differences can be found in Flanders and Slovakia in this ﬁeld?